The Influence of Entrepreneurial Competence and Personal Independence on Business Success in Micro Businesses in Tamalate Sub-District Makassar City - Sitti Hasbiah (Indonesian Journal of Business and Entrepreneurship Research, 2023)
This study aims to determine the effect of entrepreneurial competence and personal independence on the success of micro businesses in Tamalate Sub-District, Makassar City. This research is categorized as quantitative descriptive research with a population of 230 micro business actors in Tamalate Sub-District, Makassar City. Data collection in this study was carried out using observation, questionnaire, interview, and documentation techniques. The analysis technique used is descriptive statistics and inferential statistics. The results of this study indicate that entrepreneurial competence and personal independence together have a positive and significant effect on the success of micro businesses in Tamalate Sub-District, Makassar City. So, it can be said that there is a positive and significant influence between entrepreneurial competence and personal independence on the success of micro businesses in Tamalate Sub-District, Makassar City.